The microstructure and mechanical properties of selectively laser melted AlSi10Mg: The effect of a conventional T6-like heat treatment - Aboulkhair, Nesma T.; Maskery, Ian; Tuck, Christopher; Ashcroft, Ian; Everitt, Nicola M. (Elsevier, 2016)
Selective laser melting (SLM) of aluminium is of research interest because of its potential benefits to high value manufacturing applications in the aerospace and automotive industries. In order to demonstrate the credibility of SLM Al parts, their mechanical properties need to be studied. In this paper, the nano-, micro-, and macro-scale mechanical properties of SLM AlSi10Mg were examined. In addition, the effect of a conventional T6-like heat treatment was investigated and correlated to the generated microstructure. Nanoindentation showed uniform hardness within the SLM material. Significant spatial variation was observed after heat treatment due to phase transformation. It was found that the SLM material's micro-hardness exceeded its die-cast counterpart. Heat treatment softened the material, reducing micro-hardness from 125±1 HV to 100±1 HV. An ultimate tensile strength (333 MPa), surpassing that of the die cast counterpart was achieved, which was slightly reduced by heat treatment (12%) alongside a significant gain in strain-to-failure (~threefold). Significantly high compressive yield strength was recorded for the as-built material with the ability to withstand high compressive strains. The SLM characteristic microstructure yielded enhanced strength under loading, outperforming cast material. The use of a T6-like heat treatment procedure also modified the properties of the material to yield a potentially attractive compromise between the material's strength and ductility making it more suitable for a wider range of applications and opening up further opportunities for the additive manufacturing process and alloy combination.